Does blended learning bring about less boredom to EFL teachers? - Farzaneh Kazemi; Farnaz Heyran Kahnamuei (Technology in Language Teaching & Learning)
Considering the growing prevalence of the implementation of technology in the field of language education, the widely used approach called “blended Learning”, defined as a mixture of face-to-face education with computer-assisted instruction is reported to be beneficial in several aspects such as improved performance, a high-quality English learning context, and better performance in the integrated skills of the English language. However, a number of shortcomings, such as a greater load of responsibility, and the lack of familiarity with modern learning methods have also been reported in the literature. Taking the pivotal, yet underestimated role of teacher boredom in education quality, the study set out to explore whether this approach, as compared to traditional ones, brings about more boredom among EFL teachers. With the inclusion of 78 EFL teachers, the research used a questionnaire developed by Kruk et al., (2024), named the “L2 teacher boredom scale”, distributed via a Google Forms link. The scale involves five main factors, being “(F1) repetitiveness and monotony, (F2) inefficient communication, (F3) lack of satisfaction, (F4) lack of creativity, and (F5) lack of interest”. The answers provided by participants comparing boredom in traditional versus blended teaching methods revealed that there is a statistically significant relationship between the use of blended teaching and teachers’ boredom, in terms of all factors concerned. Moreover, repeated measures ANOVA as used to investigate the effect of demographic features on the level of boredom, and no statistically significant effect was observed. Considering the over-reliance of current teaching and educational systems on technology, the study is believed to provide practical pedagogical implications for stakeholders in education, e.g., ongoing professional development, participatory instructional design, balanced curriculum structure, and monitoring emotional well-being.